Age, tectonic setting and regional implications of the Chiang Khong volcanic suite, northern Thailand - Sandra M. Barr (2018)
The Chiang Khong volcanic suite forms the northeastern part of the Tak-Chiang Khong volcanic belt in the Sukhothai terrane of northern Thailand. It consists mainly of subaerial andesitic to rhyolitic tuffaceous rocks. A rhyolitic tuff yielded a Middle Triassic U-Pb (zircon) age of 232.9 ± 0.4 Ma. The suite displays calc-alkalic chemical trends and Nb, P, and Ti depletion characteristic of subduction-related magmatism. Based on petrological similarities, the suite is correlated with the c. 240 Ma Lampang volcanic rocks located farther to the SW in the Tak-Chiang Khong belt, and with volcanic rocks of similar age in the Lincang-Jinghong belt in Yunnan, in the western part of the Simao block. These correlations support the placement of the Palaeo-Tethyan suture to the west of the Sukhothai terrane.